2021
DOI: 10.1136/thoraxjnl-2020-215449
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent TB: a systematic review and meta-analysis of the incidence rates and the proportions of relapses and reinfections

Abstract: BackgroundA recurrent tuberculosis (TB) episode results from exogenous reinfection or relapse after cure. The use of genotyping allows the distinction between both.MethodsWe did a systematic review and meta-analysis, using four databases to search for studies in English, French and Spanish published between 1 January 1980 and 30 September 2020 that assessed recurrences after TB treatment success and/or differentiated relapses from reinfections using genotyping. We calculated person years of follow-up and perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 22 publications
3
28
0
Order By: Relevance
“…A recent systematic review reports higher rates of recurrent TB in high HIV prevalence areas, 65 consistent with a prior systematic review that reported a TB recurrence rate of 4.5 (3.2–5.8) in PLHIV compared to 1.9 (1.2–2.7) in people without HIV per 100 person-years. 66 Post-TB lung disease following TB completion is an additional concern.…”
Section: Challenges That Drive Tb-related Mortality In Plhivsupporting
confidence: 84%
“…A recent systematic review reports higher rates of recurrent TB in high HIV prevalence areas, 65 consistent with a prior systematic review that reported a TB recurrence rate of 4.5 (3.2–5.8) in PLHIV compared to 1.9 (1.2–2.7) in people without HIV per 100 person-years. 66 Post-TB lung disease following TB completion is an additional concern.…”
Section: Challenges That Drive Tb-related Mortality In Plhivsupporting
confidence: 84%
“…A study conducted a meta-analysis on the proportion of exogenous reinfection in recurrent TB ( Vega et al 2021 ), but a systematic exploration of related factors is still lacking. The purpose of our study was to provide an in-depth exploration of the risk factors that affect the types of recurrent TB (reactivation and reinfection) according to a meta-analysis.…”
Section: Introductionmentioning
confidence: 99%
“…After successful treatment, the incidence of recurrent TB across 145 countries was estimated 2.26 per 100 person-years (at a 95% CI, range: 1.88–2.72), ranged from 0.05 to 29.52 [ 5 ]. This reflects the heterogeneity of study designs, the definition of recurrence, local TB incidence and the study populations analyzed.…”
Section: Introductionmentioning
confidence: 99%